2019
DOI: 10.1002/anie.201900248
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization of 3‐Nitroindoles by a Phosphine‐Catalyzed Enantioselective [3+2] Annulation Reaction

Abstract: The dearomatization of 3-nitroindoles through ac hiral-phosphine-mediated [3+ +2] annulation reaction is described. This method makes use of readily available 3nitroindoles as an aromatic feedstocka nd rapidly delivers aw ide range of cyclopentaindoline alkaloid scaffolds in ah ighly enantioselective manner.N otably,p hosphine-triggered cyclization has not been utilized previously in a dearomatization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…103 104, 105 It was recently demonstrated that the enantioselective dearomatization of the indole ring through a phosphinecatalyzed [3+2] annulation reaction was significantly influenced by the aromatic character of the indole. 106 The computational studies have shown that the aromaticity of the indole ring was modified by the substituents on the pyrrole ring. Notably, the aromaticity index of the indole ring, including NICS(1)zz and corresponding ASE obtained via Schleyer's protocol, 94 correlated with the yields of the reaction very well.…”
Section: Aromaticity and Reactivitiesmentioning
confidence: 99%
“…103 104, 105 It was recently demonstrated that the enantioselective dearomatization of the indole ring through a phosphinecatalyzed [3+2] annulation reaction was significantly influenced by the aromatic character of the indole. 106 The computational studies have shown that the aromaticity of the indole ring was modified by the substituents on the pyrrole ring. Notably, the aromaticity index of the indole ring, including NICS(1)zz and corresponding ASE obtained via Schleyer's protocol, 94 correlated with the yields of the reaction very well.…”
Section: Aromaticity and Reactivitiesmentioning
confidence: 99%
“…Our group has recently been active in this research field, and particularly we developed peptide‐based multifunctional phosphonium salts and applied them to numerous asymmetric transformations especially including various cycloaddition reactions [10] . Recently, for the asymmetric [3+2] cycloaddition of 2‐nitrobenzofurans and 2‐nitroindoles, [11] the research groups of You, [12] Yuan, [13] Lu, [14] Zhang [15] and others [16] also contributed significantly. Inspired by these important progresses and our recent success in phosphonium catalysis, we became interested in exploring efficient and utilitarian strategies by combining phosphonium salt catalysis and enantioselective dearomatization process to enable the asymmetric construction of synthetically challenging and biologically important polycyclic molecules particularly bearing trifluoromethyl units.…”
Section: Figurementioning
confidence: 99%
“…Recent studies have shown that the substitution at the C-3 position with electron-withdrawing groups (3-EWG-indoles) not only endows these structures with important pharmaceutical/therapeutic activities [13][14][15][16][17][18][19][20][21], but also it converts them into versatile synthetic molecular platforms in heterocyclic chemistry, such as, in dearomatization-based synthetic disconnections [22]. The catalytic asymmetric dearomatization of 3-nitroindoles constitutes an iconic example of this synthetic potential [23][24][25][26][27][28][29][30][31][32][33][34]. The most traditional synthetic approach to these functionalized indoles relies on the Friedel-Crafts acylation of preformed indoles [35][36][37].…”
Section: Introductionmentioning
confidence: 99%